Purification and Characterization of Protease from Protease-producing Bacteria Isolated from Tofu Whey - Wardani, Agustin Krisna; Nindita, Lia Oriana (Jurnal Teknologi Pertanian, 2012)
In this study, soybean liquid waste (tofu whey), was used to isolate the protease- producing bacteria. The aim of this research is to purify and characterize the protease isolated from protease producing bacteria. Thirty isolates were obtained from isolation and screening of protease-producing bacteria from tofu whey. Â One isolate, LnA4, had the highest protease activity (0.123 U/mg). The protease was purified by ammonium sulphate and dialysis resulted an enzyme with specific activity of 7.13 U/mg with purification fold 12.96. The maximum protease activities for the enzyme was attained at 37 â°C, pH 7.5 and 0,6% of casein concentration. The KM and Vmax of the enzyme were 0.269 mg.mL-1 and 0,207 mg.mL-1.minute-1, respectively. Â The molecular weight of the enzyme was determined as 29.71 kDa on Â SDS-PAGE and zimogram. Keywords: isolation, purification, characterization, protease, tofu whey